The effect of interpersonal communication intensity and openness on self-esteem among communication students at Universitas Muhammadiyah Yogyakarta - Muslimah, Muslimah; Rasyid, Erwin (COMMICAST, 2025)
Self-esteem is a crucial component of students’ psychological well-being and is strongly shaped by the quality of interpersonal communication. This study investigates the influence of communication intensity and openness on the self-esteem of Communication Science students at Universitas Muhammadiyah Yogyakarta. A quantitative survey was conducted with 81 randomly selected respondents using a validated questionnaire. Data were analyzed through Pearson correlation and simple linear regression. The results indicate that openness has a moderate positive correlation with self-esteem (r = 0.402, p < 0.05), while intensity shows a lower yet significant correlation (r = 0.363, p < 0.05). Together, the two variables explain 16.2% of the variance in self-esteem, although only openness demonstrates a near-significant individual effect. These findings suggest that the quality of communication is more influential than its frequency in shaping self-esteem. The study contributes to communication science by extending Social Penetration Theory within the Indonesian context and emphasizing openness as a key factor in student development. Practically, the findings encourage universities to integrate open-communication training and peer-mentoring programs to support students’ psychological well-being. The main limitation of this study is the relatively small sample and focus on a single program, which restricts generalizability. Future research should involve larger and more diverse populations and include additional variables such as emotional intelligence and social support to provide a more comprehensive understanding.